Substitution possibilities and determinants of energy intensity for China - Ma, H.; Oxley, Leslie; Gibson, J. (Elsevier Science, 2009)
This paper measures technological change, factor demand and inter-factor and inter-fuel substitutability measures for China. We use individual fuel price data and a two-stage approach to estimate total factor cost functions and fuel share equations. Both inter-factor and inter-fuel substitution elasticities are calculated and the change in energy intensity is decomposed into its driving forces. The results suggest that energy is substitutable for capital regionally and for labor nationally. Capital substitutes for energy more easily than labor does. Energy intensity changes vary by region but the major drivers seem to be "budget effect" and the adoption of energy-intensive technologies, which might be embodied in high-level energy-using exports and sectors, capital investment and even old technique and equipment imports. Whether the trend in rising energy intensity continues will be significant for China and the rest of the world. © 2009 Elsevier Ltd. All rights reserved.